(untitled) - Perreault, William D.; William D. Perreault; E. Jerome McCarthy (Boston, Mass)
A shorter, but comprehensive version of "Basic Marketing", 11th edition. New material is retained, but excess verbiage and detailed explanations are paired down
Includes bibliographical references and indexes
Keywords: Marketing